Alleviation of hepatic fibrosis and autophagy via inhibition of transforming growth factor‐β1/Smads pathway through shikonin. Issue 1 (10th July 2018) - Liu, Tong; Xu, Ling; Wang, Chengfen; Chen, Kan; Xia, Yujing; Li, Jingjing; Li, Sainan; Wu, Liwei; Feng, Jiao; Xu, Shizan; Wang, Wenwen; Lu, Xiya; et al.
Abstract: Background and Aim: Liver fibrosis is a worldwide clinical challenge during the progression of chronic liver disease to liver cirrhosis. Shikonin is extracted from the root of Lithospermum erythrorhizon with antioxidant, anti‐inflammatory, anticancer, and wound‐healing properties. The study aims to investigate the protective effect of shikonin on liver fibrosis and its underlying mechanism. Methods: Two liver fibrosis models were established in male C57 mice by intraperitoneal injection of CCl4 or bile duct ligation. Shikonin was administered orally three times weekly at a dose of 2.5 or 5 mg/kg. Protein and mRNA expressions were assayed by quantitative real‐time polymerase chain reaction, Western blotting, and immunohistochemical staining. Results: Shikonin significantly inhibited activation of hepatic stellate cells and extracellular matrix formation by downregulating the transforming growth factor‐β1 expression and maintaining the normal balance between metalloproteinase‐2 and tissue inhibitor of metalloproteinase‐1. Shikonin also decreased hepatic stellate cell energy production by inhibiting autophagy. Conclusions: The results confirmed that shikonin attenuated liver fibrosis by downregulating the transforming growth factor‐β1/Smads pathway and inhibiting autophagy.